Role of Broccoli Fiber for Amoxicillin Delivery and Gut Biome Survival - Amruthavalli, Gatla Venkata; Vijayalakshmi, Arumugam (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim Broccoli fiber has enormous safety net as well as high pre-biotic value. Amoxicillin is although an effective drug against infections is equally harmful to gut microbiota and therefore the above side-effect impedes the use of amoxicillin. The present study deals with evaluating the dual benefits of the partially depolymerized fiber to deliver amoxicillin when the same is used as base fiber in lieu of Micro Crystalline Cellulose (MCC), as well as in protecting the gut microbiota by serving as transient refuge cum pre-biotic material. Materials and Methods Broccoli was partially depolymerized by alkali treatment and subjected to pre formulation studies such as powder microscopy, ash content analysis, particle density and angle of repose. Then using the partially depolymerized fiber formulated tablet dosage form of amoxicillin (500 mg). Using XRD and FTIR the interaction of partially depolymerized fiber with amoxicillin was studied. Release pattern of amoxicillin from the fiber and selective preference and binding of various probiotic species was studied simultaneously using different simulated gut systems. Results Study findings show that broccoli fiber instantaneously released amoxicillin and the space vacated by amoxicillin is being occupied rapidly by various probiotic species and thereby could survive the amoxicillin effect. The parachute effect of the fiber to probiotic is also reconfirmed by simulated gut digestion process and findings show the post gut digested fiber also exhibited significant prebiotic value. The fiber also met various physiochemical parameters that of MCC and also formulation dependent characteristics such as flow, compressibility and disintegration. Zero modification to the fiber vis-à-vis amoxicillin also established by X-ray Diffraction (XRD) and Fourier-Transform Infrared Spectroscopy (FTIR). Conclusion Probiotic microbes when encounter amoxicillin shows greater preference towards the partially depolymerized fiber and seek parachute effect from the fiber. Broccoli fiber is useful to deliver amoxicillin and also protect gut microbiome.
Keywords: Amoxicillin delivery; Broccoli; Tablet excipients; Probiotic protection; Probiotics